IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE COOPERATIVE SCRIPT UNTUK MENINGKATKAN PROSES PEMBELAJARAN IPS KELAS IVB SD NEGERI 146 PEKANBARU - Syafitri, Asri Cahya Syafitri Cahya; Marhadi, Hendri Marhadi; ', Munjiatun (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This research was aimed to increase learning process and students’ achievement of social lesson in IVB grade year of 2014/2015. The subject of this research is students IVB grade of State Elementary School 146 Pekanbaru which is total of 36 students, consisted of 21 girls and 15 boys. This was a classroom research which has two cycles which was conducted on April 16th to May 2nd 2015. The data shown that either learning process or students’ achievement increased. This was found from students’ and teacher’s scores in learning process increased. First cycle at the first meeting teacher’s activity was 58, 33% categorized as enough and increased 4, 17% at the second meeting as 62, 5% categorized as good. Meanwhile at the second cycle at the first meeting the percentage of teacher’s activity increased as 79, 17% categorized as good and in the second meeting it increased as 8,33% so the percentage became 87,5% categorized as very good. While students’ activities in learning process also increased. At the first cycle in the first meeting, the percentage of students’ activities was 58,33% categorized as enough and the second meeting it increased as 8,34% so became 66,67% categorized as good. At the second cycle in the first meeting it increased to 79, 17 categorized as good. At the second meeting the percentage of students’ activities increased as 12, 5% became 91, 7% categorized as very good. However, students’ achievement also increased. The basic score of daily examination as 7, 93% which 23 students passed and 13 students failed. The ending of daily examination was 63, 89% and the average was 74, 17% on the passing grade. The second daily examination also increased from basic score as 18, 03% which 30 students passed and 6 students failed. The ending of second daily examination was 83, 33% and the average was 81, 11%. Based on the explanation above it can be concluded that the implementation learning through Cooperative Script increased learning process in social lesson of students IVB grade of State Elementary School 146 Pekanbaru. Key Words: Cooperative Learning Thype Cooperative Script, Learning Process